IMPORTANCE OF WINE TOURS AND CULTURAL ACTIVITIES IN EVENTS ORGANIZED IN CANADA AND SLOVAKIA WINERIES (Journal of Event, Tourism and Hospitality Studies, 2022)
The study deals with wine tourism in two countries namely Canada and Slovakia, and the discussion is focused on answering the question of how important wineries are for tourism by arranging wine tours with wine tasting and visits to cultural attractions. A case study has been used as a research method in both countries, focusing on wine tourism and cultural tourism. The information for this study was gathered through secondary research, a study visit, and teaching at Waterloo University in Canada. In Slovakia, both primary and secondary research results were gathered. Organizing events in tourist destinations can increase the destination’s significance and improve the competitiveness of tourism destinations. It is important to mention that during this event periods, the consumers' preferences change and it may influence their choice of destinations and tourism products. The ageing population and their interest in travel destinations that offer wine tasting, culinary products, and culture are other factors contributing to the growth of wine tourism and cultural tourism. It also affects where marketing and branding ideas are placed in tourist destinations.